NEED ANALYSIS OF ENGLISH DEPARTMENT STUDENTS AS THE BASIC OF MATERIAL DEVELOPMENT OF WRITING FOR GENERAL COMMUNICATION - Evie Kareviati; Rasi Yugafiati; Setya Resmini (STKIP Siliwangi, 2020)
Writing is one out of four skills that should be mastered, but Writing is the most difficult one because of its complexity in making sentence. This research is intended to identify the students’ needs related to Writing for General Communication as a subject in the second semester. The research method was qualitative. The data were obtained from test, questionnaire and interview as a triangulation. The respondents were 33 students of second semester of English Department in IKIP Siliwangi Bandung. The data from test showed that students’ difficulties in writing dealing with linguistic problem. In addition, the data from questionnaire revealed that respondents have various educatioal experiences, their first language, their interests, their cultural background and different purposes for learning English. The result showed that almost 100% of students want to learn tenses, kinds of text, generic structure and punctuation. It indicates that there is a need to design a coursebook in Writing General Communication based on the students’ need. It is used as the basic for designing a textbook in Writing for General Communication subject. Need analysis, Material development, Writing for General Communication